2021
DOI: 10.3390/plants10102224
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Selenium and Boron Mitigate Salt-Induced Oxidative Damages in Glycine max L.

Abstract: The present investigation was executed with an aim to evaluate the role of exogenous selenium (Se) and boron (B) in mitigating different levels of salt stress by enhancing the reactive oxygen species (ROS) scavenging, antioxidant defense and glyoxalase systems in soybean. Plants were treated with 0, 150, 300 and 450 mM NaCl at 20 days after sowing (DAS). Foliar application of Se (50 µM Na2SeO4) and B (1 mM H3BO3) was accomplished individually and in combined (Se+B) at three-day intervals, at 16, 20, 24 and 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…To adapt to the high-salinity soil environment, crops often adjust their own osmotic balance, ion distribution, reactive oxygen species (ROS), photosynthesis, and other physiological processes, 4 to reduce the toxicity of salt to their growth and development. Some studies have shown that crops respond to salt stress by reducing the osmotic potential of cells and enhancing the water absorption capacity of roots by regulating inorganic ions 5 or synthesizing and accumulating organic substances 6 in cytoplasm, to alleviate the osmotic stress caused by salt. Besides, under salt stress, crops increase the activity of antioxidant enzymes 7 and the content of small molecular antioxidants (ascorbic acid, 8 glutathione, 9 tocopherol, 10 etc.…”
Section: Introductionmentioning
confidence: 99%
“…To adapt to the high-salinity soil environment, crops often adjust their own osmotic balance, ion distribution, reactive oxygen species (ROS), photosynthesis, and other physiological processes, 4 to reduce the toxicity of salt to their growth and development. Some studies have shown that crops respond to salt stress by reducing the osmotic potential of cells and enhancing the water absorption capacity of roots by regulating inorganic ions 5 or synthesizing and accumulating organic substances 6 in cytoplasm, to alleviate the osmotic stress caused by salt. Besides, under salt stress, crops increase the activity of antioxidant enzymes 7 and the content of small molecular antioxidants (ascorbic acid, 8 glutathione, 9 tocopherol, 10 etc.…”
Section: Introductionmentioning
confidence: 99%
“…In our experiment, we found that soybean plants exposed to 300 and 450 mM NaCl stress showed 35 and 55%, respectively reduction in plant height. Moreover, shoot FW and DW were declined by 43 and 41%, respectively at 150 mM NaCl stress [45].…”
Section: Growthmentioning
confidence: 94%
“…Two soybean genotypes viz. Shohag and AGS 313 were tested against salinity (50 and 100 mM NaCl) for Plant Stress Physiology -Perspectives in Agriculture different durations (15,30,45,60, and 80 d) and it was observed that salt stress caused a reduction in RWC, water retention capacity, leaf water potential, and exudation rate in a concentration and duration-dependent manner [70]. The decline in exudation rate indicated the lower flow of water into plants which is associated with lower water potential and eventually RWC.…”
Section: Water Relationmentioning
confidence: 99%
See 2 more Smart Citations